2019
DOI: 10.3389/fphar.2019.00666
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes, Macrophages, and Metabolic Disease in Atherosclerosis

Abstract: Atherosclerotic cardiovascular disease (CVD) is a lipid-driven chronic inflammatory disease, in which macrophages are responsible for taking up these lipids and driving disease progression. Over the years, we and others have uncovered key pathways that regulate macrophage number/function and identified how metabolic disorders such as diabetes and obesity, which are common risk factors for CVD, exacerbate these pathways. This ultimately accelerates the progression of atherosclerosis and hinders atherosclerotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 109 publications
(159 reference statements)
0
89
3
3
Order By: Relevance
“…EC-derived chemokines bind to their cognate receptors on the surfaces of monocytes and recruit them toward the inflamed endothelium. Following this, selectin-based rolling and integrin-based attachment of monocytes to the ECs cause their migration toward the subendothelial region, where they develop into lipid-laden macrophages or foam cells later on (42).…”
Section: Effects Of T2dm On the Circulatory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…EC-derived chemokines bind to their cognate receptors on the surfaces of monocytes and recruit them toward the inflamed endothelium. Following this, selectin-based rolling and integrin-based attachment of monocytes to the ECs cause their migration toward the subendothelial region, where they develop into lipid-laden macrophages or foam cells later on (42).…”
Section: Effects Of T2dm On the Circulatory Systemmentioning
confidence: 99%
“…Finally, cholesterol-laden foam cells are generated. They promote inflammation and progression of the disease through the synthesis and secretion of cytokines, chemokines, ROS, and matrix metalloproteinases (MMPs) ( Figure 2C) (42). Foam cells lose their migratory potential, die by apoptosis and generate a necrotic core within the atherosclerotic plaque (143).…”
Section: Macrophagesmentioning
confidence: 99%
“…Diabetes is associated with not only increased number of circulating monocytes [32], but also activation of inflammatory monocytes and macrophages [33]. Moreover, a study enrolling patients with severe heart failure suggested a negative correlation between left ventricular ejection fraction (LVEF) and the abundance of CCR2-positive macrophage in the cardiac tissue [18].…”
Section: Plos Onementioning
confidence: 99%
“…Current evidence also suggests that neutrophilia may promote early lesion development. Monocytosis in Apoe −/− mice suggests a simultaneous increase in production and a decrease in cell clearance; with the underlying mechanism due in part to an increase in granulocyte colony stimulating factor (G-CSF) coupled with cholesterol dysregulation which increases HSPC proliferation and skewing of leukocyte production towards monocytes and neutrophils (5,44,45,97,98). In addition to this, cholesterol-related pathways control the proliferation of progenitor hematopoietic stem cells (25,81,82,99).…”
Section: Hypercholesterolemia and Splenic Emh In Atherosclerosismentioning
confidence: 99%